Предмет: Математика,
автор: eldarmikoj
36. Упростите выражение: 1) (3-√2). (5 + √8); 3) (2 + √15). (√5 -√3); 2) (4-√3)(√3+6); 4) (3/5+√3).(√3-4/5);
Приложения:
Ответы
Автор ответа:
1
Ответ:
1. (3-√2)(5+√8) = (3-√2)(5+2√2) = 15+6√2-5√2-4 = 11+√2
2. (4-√3)(√3+6) = 4(√3+6)-√3(√3-6) = 4√3+24-3-6√3 = -2√3+21
3. (2+√15)(√5-√3) = 2(√5-√3)+√15(√5-√3) = 2√5-2√3+√75-√45 = 2√5-2√3+5√3-3√5 = -5+3√3
4. (3√5+√3)(√3-4√5) = 3√15-60+3-4√15 = -√15-57
baudinovadiana:
блин, ща доделаю
Похожие вопросы
Предмет: Право,
автор: Аноним
Предмет: Биология,
автор: DanielLandsberg
Предмет: Литература,
автор: zimbaldavid2000
Предмет: МХК,
автор: cprovodok
Предмет: Қазақ тiлi,
автор: baxievasaida